Expression analysis and significance of PD-1, LAG-3 and TIM-3 in human non-small cell lung cancer using spatially-resolved and multiparametric single-cell analysis. - Datar, Ila (Clin Cancer Res, 2019)
PURPOSE: To determine the tumor tissue/cell distribution, functional associations and clinical significance of PD-1, LAG-3 and TIM-3 protein expression in human non-small cell lung cancer (NSCLC). EXPERIMENTAL DESIGN: Using multiplexed quantitative immunofluorescence (QIF), we performed localized measurements of CD3, PD-1, LAG-3 and TIM-3 protein in >800 clinically annotated NSCLCs from three independent cohorts represented in tissue microarrays. Associations between the marker’s expression and major genomic alterations were studied in The Cancer Genome Atlas-NSCLC dataset. Using mass cytometry (CyTOF) analysis of leukocytes collected from 20 resected NSCLCs, we determined the levels, co-expression and functional profile of PD-1, LAG-3 and TIM-3 expressing immune cells. Finally, we measured the markers in baseline samples from 90 advanced NSCLC patients treated with PD-1 axis blockers and known response to treatment. RESULTS: PD-1, LAG-3 and TIM-3 were detected in tumor infiltrating lymphocytes (TILs) from 55%, 41.5% and 25.3% of NSCLC cases, respectively. These markers showed a prominent association with each other and limited association with major clinicopathologic variables and survival in cases not receiving immunotherapy. Expression of the markers was lower in EGFR-mutated adenocarcinomas and displayed limited association with tumor mutational burden. In single-cell CyTOF analysis, PD-1 and LAG-3 were predominantly localized on T-cell subsets/NKT cells; while TIM-3 expression was higher in NK cells and macrophages. Co-expression of PD-1, LAG-3 and TIM-3 was associated with prominent T-cell activation (CD69/CD137), effector function (Granzyme-B) and proliferation (Ki-67), but also with elevated levels of pro-apoptotic markers (FAS/BIM). LAG-3 and TIM-3 were present in TIL subsets lacking PD-1 expression and showed a distinct functional profile. In baseline samples from 90 advanced NSCLC patients treated with PD-1 axis blockers, elevated LAG-3 was significantly associated with shorter progression-free survival. CONCLUSION: PD-1, LAG-3 and TIM-3 have distinct tissue/cell distribution, functional implications and genomic correlates in human NSCLC. Expression of these immune inhibitory receptors in TILs is associated with prominent activation, but also with a pro-apoptotic T-cell phenotype. Elevated LAG-3 expression is associated with insensitivity to PD-1 axis blockade suggesting independence of these immune evasion pathways.